Revisiting nocturnal heart rate and heart rate variability in insomnia: A polysomnography‐based comparison of young self‐reported good and poor sleepers. (23rd February 2021) - Cosgrave, Jan; Phillips, Jessica; Haines, Ross; Foster, Russell G.; Steinsaltz, David; Wulff, Katharina
Abstract: Primary insomnia is often considered a disorder of 24‐hr hyperarousal. Numerous attempts have been made to investigate nocturnal heart rate (HR) and its variability (HRV) as potential pathophysiological hallmarks of altered arousal levels in insomnia, with mixed results. We have aimed to overcome some of the pitfalls of previous studies by using a young, medication‐free, age‐ and gender‐matched population consisting of 43 students aged 18–30 years half with a subthreshold insomnia complaint. We employed at‐home ambulatory polysomnography and compared this attenuated insomnia group to a good sleeping group. The poor sleepers had significantly higher wake after sleep onset, arousal count, mean HR in all sleep stages (with the exception of Stage 1) and lower sleep efficiency. Consistent with previous research, we also found a significant group‐by‐sleep stage interaction in the prediction of nocturnal HR, highlighting the insomnia group to have a lower wake–sleep HR reduction compared to good sleepers. When restricting our analyses to insomnia with objectively determined short sleep duration, we found significantly lower standard deviation of RR intervals (SDNN; a measure of HRV) compared to good sleepers. Taken together, this lends credence to the hyperarousal model of insomnia and may at least partially explain the increased prevalence of cardiovascular morbidity and mortality observed in patients with insomnia.